Identifikasi Pengaruh Adanya Industri Fashion Terhadap Tingkat Pendapatan di Kecamatan Banjarsari Surakarta - Hartomo, Feri; , Indah Pratiwi, ST., MT; , Muchlison Anis ST.,MT (2016)
Fashion industry contributor income significant for economic growth in certain areas .The study is done to know how much the role of fashion industry on economic growth , in addition to know the influence of the work , many years working , and sales volume of income levels in district banjarsari , the city surakarta .Data collection obtained from interview , observation , and documentation it is also uses a questionnaire with scales likert's filled by workers fashion industry in district banjarsari , the city surakarta .Methods used is linear regression multiple , a correlation coefficient , the t , test results processing f. using analysis multiple linear regression locations that the value of adjusted r square 0,444 or can specified with a value 44,4 % , which means for the ability to work , many years working , and sales volumes ( independent ) shows that fashion capable of creative industry.